Wagner’s Law – Evidence from Bulgaria - Assenova, Kamelia; Rusev, Nikolay (Research Papers, 2025)
Wagner’s law has been an object of interest amongst the economists for years. In its core, the law propagates the leading role of economic growth, which inevitably causes the expansion of government size. During the last decades the interests to the Wagner’s hypothesis has been reborn due to adopting recent time series econometric methods. In the light of modern time series analyses a correlation does not necessarily imply presence of causality. Thus, the objective of the current study is to examine and validate the relationship between government expenditure (at aggregate level) and economic growth for Bulgaria. We start our research by adopting the most popular functional forms of Wagner’s law. Furthermore, we test the OLS models for causal relationship between variables. We do that employing Engle and Granger (1987) procedure as well as Granger causality test. The coefficients of elasticity we acquire are close to 1 without exceed it. The coefficient of unit elasticity implies that the rate of growth of both variables in the bivariate models is approximately equal. The results from causality tests suggest there is one – directional causality, running from economic growth to government expenditures, which is consistent with Wagner’s view. Keeping account for the fact we are working with aggregate indicators we assume that the potential direction from government expenditure to GDP is result of the different influences (including the elasticity and transmission channels) the disaggregate expenditures have on the economic growth. As an instance, the most distinct difference can be observed in the nature of the current and capital expenditures which exhibit divergent behavior in relation to the economic growth. So, we adopt the view that although the impact of government spending on GDP is hard to detect on aggregate level, such causality is possible to get on disaggregate level. The last assumption is beyond the scope of the current paper and is an educated proposal for further research.